Tablet adoption and mobile learning impact in high school - Ndlovu, Lerato Kim; Mtshali, Thokozani Isaac (Jurnal Inovasi Teknologi Pendidikan, 2025)
This study examines the challenges of integrating mobile learning and tablet adoption in Tshwane West high schools, where inconsistent device availability, infrastructure limitations, and varying digital confidence hinder effective use. It explored how educators prepare learners for mobile learning, the effectiveness of training programmes for tablet adoption, and strategies to optimize mobile learning. Using a qualitative approach, data were collected from nine educators across three urban and township schools through semi-structured interviews, classroom observations, and document analysis. Findings show generally positive attitudes toward tablets, with noted improvements in lesson delivery and student engagement. However, sustained integration requires reliable technology access, continuous educator-focused professional development, and robust technical and administrative support. The study recommends incorporating collaborative projects, quizzes with immediate feedback, and multimedia presentations in lessons to enhance learner motivation and performance. For future research, longitudinal studies are suggested to evaluate the lasting effects of mobile learning on academic outcomes and to investigate institutional and infrastructural barriers in varied educational contexts. These insights will inform more effective policies and practices to advance digital education transformation in South African schools.